An Update on Factor XI Structure and Function - Mohammed, Bassem M. (Thromb Res, 2017)
Factor XI (FXI) is the zymogen of a plasma protease, factor XIa (FXIa), that contributes to thrombin generation during blood coagulation by proteolytic activation of several coagulation factors, most notably factor IX (FIX). FXI is a homolog of prekallikrein (PK), a component of the plasma kallikrein-kinin system. While sharing structural and functional features with PK, FXI has undergone adaptive changes that allow it to contribute to blood coagulation. Here we review current understanding of the biology and enzymology of FXI, with an emphasis on structural features of the protein as they relate to protease function.